2016
DOI: 10.2136/vzj2015.04.0054
|View full text |Cite
|
Sign up to set email alerts
|

Tangent Line/Second‐Order Bounded Mean Oscillation Waveform Analysis for Short TDR Probe

Abstract: Tangent line (TL) methods and the second-order bounded mean oscillation (BMO) method have been proposed for determining the reflection positions of time domain reflectometry (TDR) waveforms, especially for short-probe TDR sensors. However, the accuracy of TL methods is limited by the multi-reflection effects of the short-probe TDR sensor, and an automatic implementation of the second-order BMO is challenging because of the superimposition of the TDR waveforms. In this study, we combined a TL method with second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…New TDR waveform analysis techniques and the use of thermo‐frequency domain reflectometry (thermo‐FDR) may provide solutions to this problem. For instance, Z. Wang et al (, ) obtained promising soil water contents by combining the tangent line methods and the second‐order bounded mean oscillation method to determine the reflection points of thermo‐TDR waveforms. The potential to address the problem of the short physical length of thermo‐TDR probes using thermo‐FDR will be discussed in section .…”
Section: Probe Design and Constructionmentioning
confidence: 99%
“…New TDR waveform analysis techniques and the use of thermo‐frequency domain reflectometry (thermo‐FDR) may provide solutions to this problem. For instance, Z. Wang et al (, ) obtained promising soil water contents by combining the tangent line methods and the second‐order bounded mean oscillation method to determine the reflection points of thermo‐TDR waveforms. The potential to address the problem of the short physical length of thermo‐TDR probes using thermo‐FDR will be discussed in section .…”
Section: Probe Design and Constructionmentioning
confidence: 99%
“…The TL‐BMO method can be used to determine the reflection positions in TDR waveforms (Wang et al, 2015). It is a prediction‐correction model based on a combination of the tangent line method and the second‐order BMO method.…”
Section: Methodsmentioning
confidence: 99%
“…The small sensing volume of the thermo‐TDR design makes it suitable for fine‐scale measurements, but in some cases restricts the representativeness of actual field conditions. In addition, short probes can limit the accuracy and precision of TDR measurements (Noborio, 2001; Schwartz et al, 2014; Wang et al, 2015). Topp et al (1984) reported that the errors in TDR θ with a 0.05‐m‐long probe were significant, with a standard deviation of 0.037 m 3 m −3 , while an improved accuracy was observed for sensors with longer probes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods are available to improve the performance of T-TDR sensors. Using an expensive cable tester or oscilloscope with a short rise time (≤200 ps) (Kelly et al, 1995) and performing data smoothing and filtering analysis on the waveforms (Wang et al, 2016) can improve TDR waveform analysis for short probes. To minimize probe deflection, Kamai et al (2015) made robust probes by increasing their diameter.…”
Section: Introductionmentioning
confidence: 99%